Penanganan Air Limpasan pada Lokasi Penambangan Batubara PT Argo On Star Provinsi Kalimantan Selatan (Jurnal Geomine, 2020)
This study aims to determine the technical feasibility and safe drainage system for the smooth operation of production activities at the mining site, the effect of runoff water on the mining location and to determine the factors that affect the conventional drainage system. From the results of observations and calculations, the total flow of water entering the sump around 55,287.36 m3 / day with an area of influence of 51,111 m2 and a rainfall intensity of 682.5 mm/hour. The conclusion of this study is that the effect of runoff water on mining activities results in decreased production. Based on research in the field, the drainage system plan focuses on surface water originating from rainwater, the average rainfall intensity at the mining site is 170.625 mm/hour and water discharge is obtained. runoff of 0.6399 m3 /s using a rational method. The factors that affect the conventional drainage system are the mining system, the topography of the mining area, the planned rainfall, the return period of rain, the intensity of the rainfall, and the catchment area.